2018
DOI: 10.32771/inajog.v6i4.844
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia is associated with the incidence of preeclampsia

Abstract: Abstract Objective: to find out  the correlation between lipid profille at trimester II of pregnancy and the incidence.of preeclampsia Method : The research  was conducted in the Polyclinic of Hasanuddin University Teaching Hospital, Department of Obstetrics and Gynecology of the Faculty of Medicine, and it network in Makassar city from March, 2015 through March, 2016. The research used was the prospective cohort design. Results : The examination of the lipid levels of 115 pregnant mothers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The result from this study showed that there was a significant difference in VEGFR-1 and lipid profile in pre-eclamptic participants compared to normotensive protein free participants. Pre-eclamptic patients in this study had significantly higher serum level of TG compared to the controls which is consistent with the findings of previous studies [20,21] . In these studies, women with pre-eclampsia had a marked increase in serum TG and this may be referred to as TG-related vasculopathy which may be one of the possible etiopathogenesis of pre-eclampsia [22] .…”
Section: Discussionsupporting
confidence: 93%
“…The result from this study showed that there was a significant difference in VEGFR-1 and lipid profile in pre-eclamptic participants compared to normotensive protein free participants. Pre-eclamptic patients in this study had significantly higher serum level of TG compared to the controls which is consistent with the findings of previous studies [20,21] . In these studies, women with pre-eclampsia had a marked increase in serum TG and this may be referred to as TG-related vasculopathy which may be one of the possible etiopathogenesis of pre-eclampsia [22] .…”
Section: Discussionsupporting
confidence: 93%